Dupilumab in papuloerythroderma of Ofuji: therapeutic efficacy and paradoxical flares in a case-based review - Liu, Teng; Zhang, Meixi; Gao, Xiaoman; Yang, Kun; Bao, Yingqiu; Zhang, Qiuli; Chang, Jianmin (The Journal of dermatological treatment, 2025)
Papuloerythroderma of Ofuji (PEO) is a rare disorder characterized by the 'deck-chair sign' and is diagnosed according to the criteria proposed by Torchia et al. in 2009. This study aims to summarize the clinical manifestations, emerging treatments, and prognosis of PEO, and to explore the efficacy and paradoxical flares associated with dupilumab treatment. We report two cases associated with dupilumab treatment and conducted a search of PubMed, Embase, the China Knowledge Resource Integrated, and the Wanfang databases using the keywords 'papuloerythroderma of Ofuji' for the period from July 2009 to October 2024. A total of 52 patients were included, with onset most commonly occurring in their 70s. The systemic treatments included dupilumab ( = 7), cyclosporine ( = 6), oral glucocorticoids ( = 5), acitretin ( = 4), methotrexate ( = 3), and apremilast ( = 1). Dupilumab was administered to seven patients, and the skin lesions improved within a short period. No adverse effects were reported in three patients, although elevated eosinophil counts accompanied by worsening lesions were observed in one patient. Our findings suggest that dupilumab is the most commonly utilized treatment for PEO; however, elevated eosinophil counts and potential exacerbation of clinical symptoms warrant attention. Additionally, Tripterygium glycosides may be an effective therapy to improve these conditions.